1998
DOI: 10.1021/jf970974j
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Carnosic Acid Content in Wild and Cultivated Rosmarinus officinalis

Abstract: The concentration of carnosic acid in a representative selection of leaves from wild and cultivated populations of Rosmarinus officinalis was determined by reversed-phase HPLC following extraction with supercritical carbon dioxide. Different sources of variability including season, genetics, leaf age, and growing origin (wild or cultivated) were considered. Variability in the carnosic acid content among rosemary leaves appears to be largely due to seasonal and environmental factors, in addition to their indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 13 publications
6
36
1
1
Order By: Relevance
“…The result indicates that the position of the leaves on sage shoot should be taken into consideration when sage plant material has been chosen for extraction of antioxidant compounds. The results are in accordance with Hidalgo et al (1998), who also found that the content of carnosic acid is the highest in youngest leaves of Rosmarinus officinalis. The authors suggested that it might be due to the fact that antioxidants as protective compounds are important at the early growth stage, where young leaves are more vulnerable and/or young leaves have a far more active metabolism, so they require higher concentrations of essential compounds needed for growing.…”
Section: Resultssupporting
confidence: 91%
“…The result indicates that the position of the leaves on sage shoot should be taken into consideration when sage plant material has been chosen for extraction of antioxidant compounds. The results are in accordance with Hidalgo et al (1998), who also found that the content of carnosic acid is the highest in youngest leaves of Rosmarinus officinalis. The authors suggested that it might be due to the fact that antioxidants as protective compounds are important at the early growth stage, where young leaves are more vulnerable and/or young leaves have a far more active metabolism, so they require higher concentrations of essential compounds needed for growing.…”
Section: Resultssupporting
confidence: 91%
“…In lipid systems, extracts with higher diterpene content were the most effective (Hopia et al, 1996), while in aqueous systems rosmarinic acid exhibited the highest antioxidant activity Cuvelier et al, 2000). Several reports have been published analysing the distribution of rosmarinic and/or carnosic acids during growth and vegetative development of rosemary leaves (Hidalgo et al, 1998;Munné-Bosch et al, 1999;Munné-Bosch and Alegre, 2000;Del Baño et al, 2003;Ibáñez et al, 2003;Munné-Bosch and Alegre, 2003), however, to our knowledge this is the first report were the influence of south UK environmental growing conditions were studied simultaneously on both rosmarinic and carnosic aids.…”
Section: Análisis De Su Actividad Antirradicalaria In Vitromentioning
confidence: 90%
“…Carnosic acid biosynthesis and accumulation take place exclusively in young rosemary leaves at the branch apices, with the diterpene molecule being partially consumed during leaf development and aging (Hidalgo et al, 1998;Brückner et al, 2014;Bo zi c et al, 2015). Beside carnosic acid, less abundant phenolic diterpenes can be measured in rosemary leaves, including carnosol (Supplemental Fig.…”
mentioning
confidence: 99%